The influence of fault current & soil resistivity on the substation grounding grid behaviour - Permal, Navinesshani; Osman, Miszaina; Mohd Ariffin, Azrul; Ab Kadir, Mohd Zainal Abidin (IEEE, 2022)
The effects of fault current and soil resistivity on grounding performance are shown in this work. The fault current and soil characteristics are modified from the real values in a case study based on an actual main intake substation grounding grid utilizing CDEGS simulation software. Grounding grids give protection against the step and touch potentials to a limited extent depending on the amplitude and period of ground-fault current that is present. Besides, the soil resistivity of the location in which a grounding grid is placed also determines the performance and safety of the system. Therefore, it is important to carry out the grounding grid assessment, utilizing the field data. The findings show that maximum step and touch voltage and grid resistance increase with fault current and soil resistivity. Although the step and touch voltages, and the grid resistance increase, as top layer soil height increases, the grounding system remains safe up to a specific height of the top layer soil, based on certain soil resistivities.